Beyond the Gold–Thiol Paradigm: Exploring Alternative Interfaces for Electrochemical Nucleic Acid-Based Sensing - Arroyo-Currás, Netzahualcóyotl (ACS sensors, 2024)
Nucleic acid-based electrochemical sensors (NBEs) use oligonucleotides as affinity reagents for the detection of a variety of targets, ranging from small-molecule therapeutics to whole viruses. Because of their versatility in molecular sensing, NBEs are being developed broadly for diagnostic and biomedical research applications. Benchmark NBEs are fabricated via self-assembly of thiol-based monolayers on gold. Although robust for rapid prototyping, thiol monolayers suffer from limitations in terms of stability under voltage modulation and in the face of competitive ligands such as thiolated molecules naturally occurring in biofluids. Additionally, gold cannot be deployed as an NBE substrate for all biomedical applications, such as in cases where molecular measurements coupled to real-time, under-the-sensor tissue imaging is needed. Seeking to overcome these limitations, the field of NBEs is pursuing alternative ligands and electrode surfaces. In this perspective, I discuss new interface fabrication strategies that have successfully achieved NBE sensing, or that have the potential to allow NBE sensing on conductive surfaces other than gold. I hope this perspective will provide the reader with a fresh view of how future NBE interfaces could be constructed and will serve as inspiration for the pursuit of collaborative developments in the field of NBEs.